Indonesia – China Economic Diplomacy in Nickel Downstreaming Policy: The Perspective of the Rule of Law and Sustainable Development - Alief Qurratul 'Ain Musafa'; Dani Muhtada (Al-Amwal : Journal of Islamic Economic Law, 2026)
Purpose – This study aims to analyze nickel downstreaming policies within the framework of Indonesia-China economic diplomacy and assess their compatibility with the principles of the rule of law, sustainable development, and Islamic economic law. This study stems from the need to provide a multidimensional analysis of the policy of banning nickel ore exports and accelerating the development of smelters as a national industrialization strategy. Method – The method used is normative legal research with a legislative, conceptual, and analytical approach. Data was obtained through a literature study of legislation, scientific literature, and related policy documents, then analyzed qualitatively through legal interpretation and normative argumentation. Result – The results of the study show that the downstreaming policy has constitutional legitimacy and strategically strengthens Indonesia's position in the global supply chain of critical minerals through investment cooperation with China. However, its implementation still faces challenges in the form of structural dependence on foreign investment, the risk of environmental degradation, and unequal distribution of economic benefits. From a sharia economic law perspective, downstreaming is normatively valid as long as the state fulfills its role as a public trustee that guarantees distributive justice and intergenerational sustainability. Implication – This research contributes to the discourse on legal and economic governance by integrating the perspectives of the rule of law, sustainable development, and Islamic economic law into a unified analytical framework. Furthermore, the study provides practical recommendations for strengthening investment governance, harmonizing regulations, and promoting fairer benefit distribution mechanisms in nickel downstreaming policies.